Sistem Pakar untuk Diagnosis Rinitis pada Anak menggunakan Metode Certainty Factor - Sitompul, Jessica Sandra; Setyaningsih, Putry Wahyu (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Expert systems can assist an expert in making decisions that are realized in the form of a program. At this time the program is very helpful in improving various fields such as health, by managing the information that has been obtained. In this research, rhinitis is raised as a topic of discussion by working with experts who are experts in the field, after collecting data through interviews, the conclusion is obtained, namely how to determine whether someone has one of the three types of rhinitis (allergic rhinitis, bacterial rhinitis, and viral rhinitis) with the symptoms experienced and with a fast and accurate process. By using the certainty factor method and applying it to a web-based expert system, it makes it easier for patients and experts to solve the problem, there are 31 types of symptoms among the three types of rhinitis diseases that are used as the basis for the expert system after that with data from 20 patients at the hospital who suffer from various symptoms of rhinitis who have been diagnosed with the disease by experts as validation data and trials it is found that the system is 100% successful in accurately diagnosing each disease in all these patients.